Indonesian English language teachers’ conceptions of critical thinking: challenge and strategy - Bachtiar Bachtiar; Juhana Juhana; Widya Rizky Pratiwi (International Journal of Evaluation and Research in Education (IJERE), 2024)
Critical thinking (CT) has already been acknowledged as a significant skill in education, including in the field of English language learning. However, very few studies have investigated the challenges and strategies in enhancing students’ CT skills in English language subjects. This qualitative research aims to investigate the Indonesian English as a foreign language (EFL) teachers’ conception of the necessity of implementing CT in EFL subject. This research is also intended to find out the challenges and strategies in encouraging students to use CT in their learning process. This research employed two research tools for data collection: questionnaires and semi-structured interviews. The study revealed that EFL teachers believe in the value of promoting CT in their teaching classroom activities. However, CT has been practically rarely unnoticed in the implementation of English language classes due to the EFL teachers’ concentration on linguistic skills, grammar instruction, and English communicative skills. The findings also found some challenges faced by the EFL teachers in implementing CT, as well as some strategies in promoting the skill. This research recommends the importance of involving Indonesian EFL teachers in a training on CT to enhance their understanding and allow them to stimulate CT among their students.